A REVIEW: THE ROLE OF SNPS IN HBB, BCL11A, HBS1L-MYB, AND MIRNA NETWORKS IN BETA-THALASSEMIA: INSIGHTS FROM IRAQI AND ASIAN POPULATIONS - Qassim Raheem, Haider; AL-Mousawi, Haider Turky Mousa; Al-Mawlah, Yasir Haider; Al-Sultani, Humam Fadel; brahim, Hussein Fadil I; Shather, Shatha Ruaidh; Hassan, Hawraa Majid; Jasim, Sajjad Haider (International Journal Multidisciplinary (IJMI), 2026)
Objective: Beta-thalassemia is a genetically heterogeneous blood disorder marked by impaired hemoglobin synthesis, resulting in chronic anemia, multi-organ complications, and changing clinical severity. This review analyzes the essential functions of single-nucleotide polymorphisms (SNPs) in the HBB, BCLⅠⅠA, and HBSⅠL-MYB genes, as well as miRNA regulatory networks, in influencing beta-thalassemia phenotypes, particularly in Iraqi and Asian populations. Method: Many research investigations conducted across Iraq and Asia have highlighted the elevated prevalence and pathogenic significance of the HBB rs334 mutation, which acts as a primary genetic determinant of the disease in these regions. Additionally, regional studies have shown strong statistical links between BCLⅠⅠA variants (rs1427407, rs11886868) and HBSⅠL-MYB variants (rs4895441, rs9399137) and higher levels of fetal hemoglobin (HbF). Results: This leads to milder phenotypes, less need for transfusions, and better clinical outcomes. These results demonstrate the vital role of genetic modifiers in influencing disease severity. Moreover, the dysregulation of microRNAs—specifically miR-144/451, miR-15a/16-1, and miR-210—has been demonstrated to impact erythropoiesis, hemoglobin switching, and inflammation, thereby further influencing disease progression. According to epidemiological statistics from the World Health Organization and recent studies, the prevalence of beta-thalassemia in Iraq is around 37.1 per 100,000 individuals, with a carrier rate varying from 1.5% to 3% in different Asian areas and peaking at 20% in some ethnic groups. Up to 20% of patients with beta-thalassemia major in Iraq are co-infected with hepatitis C virus owing to their blood transfusion requirements, underscoring the critical need for comprehensive prevention measures. Novelty: The combination of genetic markers and miRNA profiles makes it possible to use personalized diagnostic and treatment methods, especially gene- and miRNA-based therapies that target specific molecular pathways. This review underscores the necessity of tailoring genetic counseling, screening, and management strategies to accommodate unique regional genetic backgrounds and modifier effects, thereby promoting precision medicine and enhancing the quality of care for beta-thalassemia patients in Iraq, Asia, and analogous populations internationally.